If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -2 = -4 + 9n Reorder the terms: -2 + 7n = -4 + 9n Solving -2 + 7n = -4 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -2 + 7n + -9n = -4 + 9n + -9n Combine like terms: 7n + -9n = -2n -2 + -2n = -4 + 9n + -9n Combine like terms: 9n + -9n = 0 -2 + -2n = -4 + 0 -2 + -2n = -4 Add '2' to each side of the equation. -2 + 2 + -2n = -4 + 2 Combine like terms: -2 + 2 = 0 0 + -2n = -4 + 2 -2n = -4 + 2 Combine like terms: -4 + 2 = -2 -2n = -2 Divide each side by '-2'. n = 1 Simplifying n = 1
| -(w-3)=6 | | 1/2(900.00+x)=87.50 | | 3ab-4c= | | 6t-18=26+8t | | 2500=3.14(10)(10) | | 7(7x+5)=49x+35 | | 2x+3=-2+5 | | 9n-2=23+4n | | 2x+5+3+x=41 | | 12-3r=-3 | | 4x-1.8=3-4.1 | | 5x+133+8x-18=180 | | -4=3x+10 | | 2x(-7-8)=24 | | 2h+5=15 | | -7-3.4=-7x-4.8 | | 2x-5+3x-15=30 | | 0.2+0.1=0.6x-0.7 | | 2*x+12=17+5x-14 | | -12x+3y=15 | | 21-[16-(7-5)-10]+8*2= | | -4y+8=4(2y-2)-2(-16+6y) | | -3x=x(6-2) | | -3x=x(6-2) | | 8(x-2)-3(2x-1)=2(x+4)-7(x-3) | | -12=3+2k+3k | | v=3.14(r)(r)h | | X^2+11x+33=0 | | 21-6x=11-14x | | 0.03-0.4=1.85 | | 8x-48+7x-42=90 | | 12=2g |